2001
DOI: 10.1590/s0037-86822001000100005
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on enteropathogenic infections of livestock in Trinidad

Abstract: A longitudinal study was conducted on selected livestock farms to determine the prevalence of enteropathogens in diarrhoeic and non-diarrhoeic animals. The enteropathogens assayed from faecal samples and rectal swabs were bacteria (Escherichia coli, Campylobacter spp. Salmonella spp. and Yersinia enterocolitica), parasites (coccidia, gastrointestinal nematodes and Cryptosporidium spp.) and viruses (group A rotavirus and parvovirus). The prevalence of the enteropathogens in various animal species was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 10 publications
1
23
2
Order By: Relevance
“…and/or I. suis) (47.2%) was the most prevalent. Contrary to the aforementioned higher prevalence of gastrointestinal parasites ova/oocyst infection in pig, Adesiyun AA reported no evidence of nematode parasites in pigs in Trinidad and Tobago [17].…”
Section: Introductionmentioning
confidence: 80%
“…and/or I. suis) (47.2%) was the most prevalent. Contrary to the aforementioned higher prevalence of gastrointestinal parasites ova/oocyst infection in pig, Adesiyun AA reported no evidence of nematode parasites in pigs in Trinidad and Tobago [17].…”
Section: Introductionmentioning
confidence: 80%
“…from diarrhoeic foals compared with non-diarrhoeic foals, are reports that the rates of detection between both groups of foals were similar [5, 13]. Adesiyun et al [40] in a cross-sectional study of diarrhoeic and non-diarrhoeic livestock in Trinidad, similarly reported that there were no statistically significant differences in the isolation rates between animals that had diarrhoea 4.0% (21 of 523) and those that did not, 2.5% (8 of 324).…”
Section: Discussionmentioning
confidence: 99%
“…2001). However, most of the previous studies have investigated C. jejuni and C. coli in diarrhoeic animals such as cattle and sheep (Adesiyun et al. 2001; Acha et al.…”
Section: Discussionmentioning
confidence: 99%